Shaft [videorecording (DVD)] - Parks, Gordon, 1912-2006; Roundtree, Richard, 1942-; Gunn, Moses, 1929-1993; Tidyman, Ernest (Warner Home Video, 2000)
Detective John Shaft is hired by a Harlem mobster to find his kidnapped teenage daughter and finds himself up against some Mafia chieftains who want to take over a chunk of the black underworld's uptown territory.